The impact of comic stories in the face of IS terrorism terrorism To develop the artistic expression of primary school students (Journal of the College of Basic Education, 2022)
Due to the multiplicity of life requirements and the increasing pace of cognitive and technological explosion, education has to exceed the field of providing students with information to the level at which the individual is in a position to know himself through the ability to analyze, discover and conclude. The researcher sees that the educational experiences provided by the art education directly or indirectly related to the levels of visual and cognitive perception of the learner, and this is the motive that made him looking for ways to raise The imagination of the students in the primary stage in unconventional ways and in this step of the style of storytelling in dealing with the terrorist extremism represented by da'as. The importance of the present research is considered by focusing on the children of the primary stage, educationally and educationally. The childhood stage is characterized by the crystallization of abstract thinking in an integrated manner. The use of easier and clearer means associated with the senses than abstraction, and the Iraqi child, who passed through a series of difficult circumstances, some of which were internal to his family are the conditions of deprivation and some of the other external represented by the violence of terrorism and the effects of all these factors on the life The current research aims to identify the impact of comic books in the face of the advocate of the criminal terroristThe great influence was shown by the visual observation that followed the teaching of these stories, which has a clear effect on the successful responses shown by the target sample, which was reflected in their drawings. Of the planners of the curricula of art education / Ministry of Education Directorate General of the curriculum in the inclusion of this method of the story stories of the effectiveness and ability to raise the motivation and desire of students and emphasize the need for the Ministry of Culture and Information to encourage workers to supply markets The libraries in the stories of children urge to confront the terrorism that is exposed to our beloved Iraq, to ​​spread the spirit of courage, to broadcast the resistance and to confront the terrorist plots, whether for a terrorist or any other terrorist organization. One of the current research proposals is the impact of storyboards in developing mental perception on the creative thinking of primary school students and their relation to artistic expression